(untitled) (Research, Society and Development, 2025)
The aim of this study was to assess potential oral changes related to the use of electronic cigarettes through an integrative review. The presence of nicotine in the e-liquids of these devices in varying concentrations raises health concerns due to the absorption of toxic substances akin to tobacco smoke. An integrative literature review was carried out by adhering to six methodological steps: defining the topic based on established objectives; determining criteria for article inclusion and exclusion; collecting and organizing data from selected studies; evaluating the methodologies used in the research; interpreting and contextualizing the results obtained; and presenting, arguing for, and reviewing the analyzed studies. The analysis indicated that electronic cigarettes, while perceived as less harmful alternatives to conventional smoking, pose significant risks to oral health such as inflammation and mucosal lesions that may exacerbate periodontal diseases. The lack of standardization across studies highlights the need for further research. Dentists play a vital role in preventing these oral lesions by educating consumers about vaping risks.